2016
DOI: 10.1111/bdi.12394
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal subfield volumes in short‐ and long‐term lithium‐treated patients with bipolar I disorder

Abstract: Long-term, but not short-term, exposure to lithium treatment may exert neuroprotective effects on specific hippocampal subfields linked to disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
4
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 50 publications
(64 reference statements)
1
20
4
4
Order By: Relevance
“…However, insufficient information on the duration of exposure has to be considered a limitation of our study. In fact, differences in hippocampal volume were found in BP patients with short‐term and long‐term lithium treatment . Moreover, we found differences in the lifetime use of antidepressants and antipsychotics.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…However, insufficient information on the duration of exposure has to be considered a limitation of our study. In fact, differences in hippocampal volume were found in BP patients with short‐term and long‐term lithium treatment . Moreover, we found differences in the lifetime use of antidepressants and antipsychotics.…”
Section: Discussionmentioning
confidence: 60%
“…In fact, differences in hippocampal volume were found in BP patients with short-term and long-term lithium treatment. 57 Moreover, we found differences in the lifetime use of antidepressants and antipsychotics. As expected from clinical practice, BP-I patients presented a lower lifetime use of antidepressants and a higher lifetime use of antipsychotics than BP-II patients, 58,59 except in the case of BP-II patients who presented childhood trauma.…”
Section: Discussionmentioning
confidence: 78%
“…19,58 A recent cross-sectional study, which included only patients with BD-I, showed that long-term, but not short-term, exposure to lithium treatment was associated with larger total hippocampal volumes and bilateral CA2–3, left CA4-DG, left presubiculum, and right subiculum volumes. 63 In addition, it was showed that erythropoietin was associated with memory improvement and reversal of brain matter loss in the left hippocampal CA1–3 and subiculum in patients with mood disorders. 64 Regarding diagnostic implications, future studies should consider the hippocampus subfield changes presented in the current study as well as other relevant brain regions that are altered in mood disorders to build a neuroanatomical network signature using machine learning techniques, so that we are able to differentiate patients with mood disorders in regards to the diagnosis and stage of the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Lithium has received more clinical assessment of its neuroprotective capacity than any other agent, most notably in bipolar disorder. Crosssectional studies of bipolar patients have associated lithium treatment with: (a) attenuation of cortical grey matter loss and (b) maintained white matter integrity (Table 1) (Giakoumatos et al, 2015;Gildengers et al, 2015;Hajek et al, 2012Hajek et al, , 2014Hartberg et al, 2015;Pfennig et al, 2014;Poletti, Locatelli, Radaelli, Colombo, & Benedetti, 2014;Simonetti et al, 2016;van Erp et al, 2012;Zung et al, 2016), though few have correlated lithium's structural benefits with a similar improvement in brain function.…”
Section: Lithiummentioning
confidence: 99%